Passive smoking and chronic obstructive pulmonary disease: cross-sectional analysis of data from the Health Survey for England. Issue 2 (6th September 2011) - Jordan, Rachel E; Cheng, Kar Keung; Miller, Martin R; Adab, Peymané
Abstract : Objectives: There is increasing evidence that passive smoking is associated with chronic respiratory diseases, but its association with chronic obstructive pulmonary disease (COPD) requires more study. In this cross-sectional analysis of data from 3 years of the Health Survey for England, the association between passive smoking exposure and risk of COPD is evaluated. Design: Cross-sectional analysis of the 1995, 1996 and 2001 Health Surveys for England including participants of white ethnicity, aged 40+ years with valid lung function data. COPD was defined using the lower limit of normal spirometric criteria for airflow obstruction. Standardised questions elicited self-reported information on demography, smoking history, ethnicity, occupation, asthma and respiratory symptoms (dyspnoea, chronic cough, chronic phlegm, wheeze). Passive smoking was measured by self-report of hours of exposure to cigarette smoke per week. Results: Increasing passive smoke exposure was independently associated with increased risk of COPD, with adjusted OR 1.05 (95% CI 0.93 to 1.18) for 1–19 h and OR 1.18 (95% CI 1.01 to 1.39) for 20 or more hours of exposure per week. Similar patterns (although attenuated and non-significant) were observed among never smokers. More marked dose–response relationships were observed between passive smoking exposure and respiratory symptoms, but the most marked effects were on the development of clinically significant COPD (airflow obstruction plus symptoms), where the risk among never smokers was doubled (OR 1.98 (95% CI 1.03 to 3.79)) if exposure exceeded 20 h/week. Conclusion: This analysis adds weight to the evidence suggesting an association between passive smoking exposure and COPD.